Dermatitis Seboroik: Etiologi & Faktor Risiko, Patofisiologi, Diagnosis, dan Tatalaksana - Sudarmanto, Syifa Hasna; Sibero, Hendra Tarigan; Ratna, Maya Ganda; Darwis, Iswandi (CV. Jasa Sukses Abadi, 2024)
Seborrheic dermatitis is a type of chronic skin inflammation caused by the fungus Malassezia sp. which is often found among patients. The prevalence reaches 4.38% on a global scale and 2% - 30% in Asia. Often found in infantile (self-limited) and adult (chronic) patients. This disease is considered to reduce the patient's quality of life. The high number of cases and the rate of decline in patient quality of life due to seborrheic dermatitis became the basis for conducting this research. Research was conducted to collect and analyze articles that raise topics related to clinical aspects of seborrheic dermatitis. The research design used was a literature review. Article collection was carried out using relevant article search applications such as Google Scholar, PubMed, and Prospero. The articles used have a range of publication criteria in 2013-2024. Based on the articles collected, results were obtained in the form of risk factors, pathophysiology, diagnosis and management of seborrheic dermatitis. Risk factors that are considered to trigger seborrheic dermatitis include high sebaceous gland activity, low body immunity, physical environmental factors in the form of humidity and temperature, and a history of poor personal hygiene. The appearance of the disease is in the form of reddish lesions covering fine colored scales, sometimes accompanied by oil or white powder. The severity of the disease is determined through the SDASI score or Seborrhoeic Dermatitis Area Severity Index. Healing therapy aims to reduce symptoms and improve skin function. The type of therapy given is based on the lesion severity index and the patient's response to therapy.